Tradition Adaptation: Creativity and Innovation in the Sasak Community's Kecimol Performance by the Merpati Nusantara Ensemble in Mataram - Galih Suryadmaja; I Wayan Kusuma Di Biagi; Rapi Renda; Muhammad Fazli Taib Saearani; Nandi Arfian Halil; Dewi Puspita Ningsih (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study examines how tradition is adapted through creativity and innovation in the Sasak community’s Kecimol performance, with a focus on the Merpati Nusantara ensemble in Mataram. The research aims to identify how Kecimol, originally a traditional ensemble rooted in Cilokaq, has evolved into a performance that integrates modern instruments, cross-genre repertoires, portable stage designs, and the use of digital media. Using an ethnographic approach involving participatory observation, in-depth interviews, and documentation, the study highlights how the creativity of the artists and the active participation of the community as both audience and co-creators drive collective innovation. This innovation successfully preserves local identity while engaging with global trends. The adaptation demonstrates cultural resilience, sustaining the vitality of tradition amid modernization, despite intergenerational value tensions and negative stigmas. From a socio-economic perspective, Kecimol functions as an alternative income source, a social interaction platform, and a form of public entertainment. This research contributes theoretically by enriching studies on creativity and cultural adaptation, while providing practical insights for cultural preservation strategies, creative economy development, and community-based tourism. Overall, Kecimol exemplifies the Sasak community’s identity and the sustainability of traditional arts within the context of globalization.